2019
DOI: 10.15517/rbt.v68i1.36881
|View full text |Cite
|
Sign up to set email alerts
|

Morfo-anatomía del ciclo de vida del helecho Pteridium aquilinum (Dennstaedtiaceae) en cultivo in vitro

Abstract: Introducción: Pteridium aquilinum es un helecho heliófilo ampliamente distribuido en México. Es una especie pionera que usualmente se encuentra en hábitats alterados y tiene gran relevancia ecológica por sus propiedades alelopáticas, su resistencia al fuego y a condiciones de sequía. Objetivo: realizar una descripción integral de la forma y ornamentación de las esporas de P. aquilinum, así como de la morfogénesis del gametofito, incluyendo el tipo de germinación y el desarrollo protálico (resaltando su morfolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Although tailings and waste land lls are complex environments to support life, there are plant species capable of surviving in these places, such as some of pteridophytes, which are resistant to degraded environments, as they are undemanding in soil fertility, survive for long periods of drought and withstand environmental adversities well. These species cause the natural regeneration process to occur, once they begin colonization, creating conditions for other species to settle (Eslava-Silva et al 2019; Marques and Krupek 2019;Praveen and Pandey 2020).…”
Section: Intruductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tailings and waste land lls are complex environments to support life, there are plant species capable of surviving in these places, such as some of pteridophytes, which are resistant to degraded environments, as they are undemanding in soil fertility, survive for long periods of drought and withstand environmental adversities well. These species cause the natural regeneration process to occur, once they begin colonization, creating conditions for other species to settle (Eslava-Silva et al 2019; Marques and Krupek 2019;Praveen and Pandey 2020).…”
Section: Intruductionmentioning
confidence: 99%
“…These materials rich in iron sulphide (pyrite -FeS 2 ), when in contact with water and atmospheric air, undergo oxidation reactions forming acidic chemical compounds, susceptible to leaching, responsible for the acid mine drainage (AMD) process, the main environmental impact in mined areas (Bilibio et al 2020).AMD is characterized by low pH (≤ 3), presence of Al, Fe, Mn and trace elements As, Cd, Cu, Ni, Pb, Zn, Cr and Hg in compositions and concentrations that depend on the kinetics of geochemical processes, mineralogy, type and quantity of oxidized sulphide, temperature, bacteria action, among other factors speci c to each environment, which condition contamination levels, and can remain active for decades and even centuries after its production (Cunha et al 2019;Yuan et al 2019).Although tailings and waste land lls are complex environments to support life, there are plant species capable of surviving in these places, such as some of pteridophytes, which are resistant to degraded environments, as they are undemanding in soil fertility, survive for long periods of drought and withstand environmental adversities well. These species cause the natural regeneration process to occur, once they begin colonization, creating conditions for other species to settle (Eslava-Silva et al 2019; Marques and Krupek 2019;Praveen and Pandey 2020).…”
mentioning
confidence: 99%
“…Their life cycle shows alternations of heteromorphic and independent generations [11]: (I) a gametophyte phase with short-term prothallium that produces gametes and (II) a dominant sporophyte phase, represented by a corm constituted by root, stem and leaves with sporangia where meiospores are contained. When these meiospores germinate, they generate the prothallium [12]. In several fern species, it has been observed that both phases are hyperaccumulators and highly tolerant to heavy metals such as lead (Pb), arsenic (As) and Cr from polluted soils and water bodies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%